Determination of operation performance indicators of unit for mowing crops with the simultaneous incorporation of their stubble into the soil - Nadykto, Volodymyr; Golub, Gennadii; Kukharets, Savelii; Kyurchev, Volodymyr; Skliar, Oleksandr; Hutsol, Taras; Glowacki, Szymon; Nurek, Tomasz; Horetska, Iryna; Yakovenko, Anatoly; Надикто, Володимир Трохимович; Кюрчев, Володимир Миколайович; et al. (SGGW : Nature portfolio, 2024)
EN: When harvesting grain crops and forage grasses using a two-phase method, trailed and/or mounted windrowers are usually used. After their passage, stubble remains on the field, which intensively loses soil moisture under sunlight and wind. To reduce these losses, the stubble, along with the soil, is crushed using disc harrows. Due to the use of two sequentially operating units (harvesting and soil-cultivating), their total operating time increases. This does little to preserve soil moisture in the cultivated field. This article provides an example of a more effective solution to this problem. It consists of using one machine-tractor unit instead of two. The proposed combined unit mows an agricultural crop in one working pass and ensures stubble crushing and incorporation into the top layer of soil. The unit consists of a wheeled tractor with a front hitch linkage, a front windrower and a disc harrow mounted behind the tractor. It has been established that the laboriousness of compiling such a unit, considering the tractor’s transformation to reverse, is insignificant and amounts to 1442 person hours. The use of the new unit assists in reducing soil moisture losses. Over a month, it can reach 4.1–5.2% in absolute terms and 15–45% in relative ones. The combined unit movement velocity should be close to 2.5 m s−1 to ensure such a reduction in soil moisture losses. Combining two technological operations performed by one machine-tractor unit does not impair its reliability. At the same time, there is a reduction in processing time for one field by almost half and a decrease in fuel consumption per unit of performed area by 2.25 times.
Keywords: Two-harvesting method; Windrower; Windrow; Disc harrow; Soil moisture; Laboriousnes; метод дворазового збирання; валкоутворювач; валок; дискова борона; вологість ґрунту; трудомісткість